THE INFLUENCE OF MANAGEMENT INFORMATION SYSTEMS, PROCESS INNOVATION AND OPERATIONAL EFFICIENCY IN HOSPITALS - Ivana Yolanda; Kosasih; Vip Paramarta; Farida Yuliaty (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The implementation of Hospital Management Information System (SIMRS) is a solution to improve operational efficiency by integrating various aspects of services, including administration, electronic medical records, and resource management. This study aims to analyze the role of Hospital Management Information System (SIMRS) and process innovation in improving hospital operational efficiency. The method used is a literature review by collecting and analyzing sources from academic databases such as PubMed, ScienceDirect, ResearchGate, and Google Scholar in the range of 2019-2024. This review discusses the implementation of SIMRS, digitalization of health services, and optimization of medical personnel and facility management. The results show that SIMRS implementation improves administrative efficiency and service coordination, while innovations such as electronic medical records, digital queuing systems, and telemedicine contribute to improved access and quality of care. In addition to technology, efficient management of medical personnel and referral systems also had a significant impact on hospital performance. This study provides recommendations for hospital managers in designing optimal strategies for technology implementation to improve health services.